An Analysis of Firearm and Explosives Injury in Imphal: A 2 Years Autopsy Based Descriptive Study - Nani Gopal Das; Thoidingjam Bijoy Singh (Indian Journal of Forensic Medicine & Toxicology, 2022)
Deaths due to high end machineries like guns and sophisticated explosives are on increasing trends withthroughout the world. Such deaths lead to high morbidity and mortality in the human society. The present studywas conducted to explore various socio demographic characters of victims and medicolegal aspects related tofirearm and explosive injuries death. This was a descriptive cross sectional autopsy based study of all firearmand bomb blast injury deaths brought to mortuary of Regional Institute of Medical Sciences, Imphal Manipurduring the period from October 2013 to August 2015. In this study a total of 46 cases of firearm and explosivesdeath during the study period was analysed in various medico-legal aspects. Rifled firearm and bomb blast wascommonest weapon employed. Multiple injuries and head injuries were commonest cause of death. The trendsof death might help the law enforcement authorities and Government to take proactive steps to curb this menace.